Extracellular vesicle-based drug delivery systems in cancer - Ruotong Huang; Jiajun Zhu; Ru Fan; Yiting Tang; Lianlong Hu; HaeJu Lee; Shuying Chen (Extracellular Vesicle)
Extracellular vesicles are lipid bilayer-enclosed extracellular membrane vesicles secreted from cells that have gradually shown promise in cancer treatment. As an essential intercellular communication mediator, extracellular vesicles carry bioactive molecules including proteins, lipids, and nucleic acids, which aid in the control and reprogramming of cell signals and ultimately accelerate the spread of cancer. Simultaneously, extracellular vesicles have become a highly desirable option for drug delivery carriers because of the special capacity to cross boundaries and low immunogenicity. Bypassing the endosomal pathway and lysosomal degradation, they can provide medications directly, increasing their effectiveness and decreasing their negative effects. We review the extracellular vesicles’ development, drug loading techniques, and discuss their potential in clinical applications to provide new avenues for precise and targeted treatment strategies. Additionally, engineering modifications of extracellular vesicles can enhance their ability to target specific cells, improving the stability and effectiveness of cargoes, further driving the development of cancer therapy. In this review, we particularly highlight new therapeutic applications of extracellular vesicles, including the latest progress in extracellular vesicle vaccines in tumors. Nonetheless, there are still a lot of obstacles to be overcome before extracellular vesicles may be used to treat cancer. Future research needs to focus on the characteristics of extracellular vesicles from various sources and explore their specific roles in disease treatment to fully leverage the potential of extracellular vesicles in clinical applications such as drug delivery.